El proceso de formación del espacio agrario en la Cuenca del río Pardinho, R. S. Brasil - Granell, María Carmen (Geographicalia, 2017)
Physical Environment of Pardinho River Basin, covered until XIXth century by subtropical rain forest, have been suffered a high changing processes to be integrared in world economical system. Initial economic system, based on policultures crops selfmaintenance and plots very small, have been evolved to an specialized economic system, based on tobacco, and final result is the integratior in world economic market.